Caregivers' experiences with the selection and use of assistive technology. (18th August 2018) - Mortenson, W. Ben; Pysklywec, Alex; Fuhrer, Marcus J.; Jutai, Jeffrey W.; Plante, Michelle; Demers, Louise
Abstract: Qualitative data from a mixed-methods clinical trial are used to examine caregivers' experiences with the selection and use of assistive technology to facilitate care recipients' independence. Through a thematic analysis of interviews from 27 caregivers, three broad themes were identified. "A partial peace of mind" described the generally positive psychological impacts from assistive technology, mainly reduced stress and a shift in caregiving labour from physical tasks to a monitoring role. "Working together" explored the caregivers' experiences of receiving assistive technology and the sense of collaboration felt by caregivers during the intervention process. Finally, "Overcoming barriers" addressed two impediments to accessing assistive technology: lack of funding and appointment wait times for service providers. The findings suggest that assistive technology provision by prescribers plays a beneficial role in the lives of caregivers, but access to such benefits can be hampered by contextual constraints. Implications for rehabilitation: The study findings have a number of implications for rehabilitation practice: Family caregivers can be instrumental in determining what assistive technology is needed and then procured. Their involvement in the selection process is desirable because assistive technology may have both positive and negative impacts on them, and they themselves may use the devices chosen. Involving family caregivers as more active partners in the process of assistive technology provision may represent a greater time investment in the short term, but may contribute to better long-term outcomes for care recipients and caregivers as well. Limited access to funding and long appointment wait times are potential barriers to obtaining necessary assistive technologies.